2003
DOI: 10.1046/j.1471-4159.2003.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐activation of PKA and PKC in cerebrocortical nerve terminals synergistically facilitates glutamate release

Abstract: Protein kinase A and protein kinase C are involved in processes that enhance glutamate release at glutamatergic nerve terminals. However, it is not known whether these two kinases co-exist within the same nerve terminal, nor is it clear what impact their simultaneous activation may have on neurotransmitter release. In cerebrocortical nerve terminals, co-application of forskolin, which increases cAMP levels and activates protein kinase A, and 4b-phorbol dibutyrate, a direct activator of protein kinase C, synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 55 publications
(75 reference statements)
6
36
0
Order By: Relevance
“…The adenylyl cyclase activator forskolin presynaptically facilitates synaptic transmission and glutamate release at many synapses (1)(2)(3)(4)(5)(6)(7)(8)(9). Several studies have found that this presynaptic facilitation is dependent on the activation of the cAMP-dependent protein kinase (PKA) (1,2,4,8), consistent with the finding that many proteins of the release machinery are targets of PKA, such as rabphilin-3 (10), synapsins (11), Rab3-interacting molecule (RIM) 3 (12)(13)(14), and Snapin (15).…”
supporting
confidence: 53%
“…The adenylyl cyclase activator forskolin presynaptically facilitates synaptic transmission and glutamate release at many synapses (1)(2)(3)(4)(5)(6)(7)(8)(9). Several studies have found that this presynaptic facilitation is dependent on the activation of the cAMP-dependent protein kinase (PKA) (1,2,4,8), consistent with the finding that many proteins of the release machinery are targets of PKA, such as rabphilin-3 (10), synapsins (11), Rab3-interacting molecule (RIM) 3 (12)(13)(14), and Snapin (15).…”
supporting
confidence: 53%
“…It has been known that PKA activation is an important upstream event of presynaptic glutamate release (Leenders and Sheng, 2005;Millan et al, 2003;Grilli et al, 2004). This statement was consistent with our results that veratridine (4 mM) could evoke presynaptic PKA activation (data shown later) and the PKA inhibitor H89 (1 mM) could block the veratridine-induced increase in the frequency of sEPSCs (n ¼ 6, data not shown).…”
Section: Allopregnanolone Inhibits Veratridine-evoked Pka Activationsupporting
confidence: 93%
“…Presynaptic evoked glutamate release is a rather complicated process involving activation of a series of presynaptic proteins, such as ion channels and enzymes etc. Among them, PKA activation is an important upstream event of evoked glutamate release (Leenders and Sheng, 2005;Millan et al, 2003;Grilli et al, 2004). Therefore, to explore the mechanism for the inhibitory effect of allopregnanolone on evoked glutamate release, here we first observed the effect of allopregnanolone on the depolarizing agent-evoked PKA activation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our Western blot experiments, the proteins of the three chemokine receptors are present in our synaptosomal preparations and may be expressed on the plasma membranes of nerve terminals. Although synaptosomal preparations contain many families of nerve endings, glutamatergic nerve terminals in the mammalian cerebrocortex were found to be extremely abundant (ϳ80% of the total) (Millán et al, 2003); therefore chemokine receptors are likely to exist on glutamatergic terminals. Nonetheless, convincing evidence that the chemokine receptors are present on human glutamatergic terminals could only come from experiments in which one function of these terminals, i.e., glutamate release, was examined.…”
Section: Discussionmentioning
confidence: 99%